The feasibility and acceptability of an intervention to improve career adaptability skills in Olympic and Paralympic athletes - Connaughton, E. (School of Health and Human Performance, Dublin City University, 2019)
The Olympic and Paralympic Games are a pinnacle experience for athletes, coaches, support staff and their families. Conceptualized as a series of meta-career transitions, each Games is unique in its own way and present intense, emotional, physical and psychological demands on competitors. Research has shown that individuals` ability to adapt to career transitions has implications for their well-being, mental health, motivation and productivity. Consequently, the aim of this research was to develop and test an athlete transition support programme that would enhance career adaptability skills in Irish Olympic and Paralympic athletes, coaches and athlete support providers. Best practice in intervention development is to approach the design systematically utilizing prior evidence and theory, and to subsequently pilot the intervention to assess key barriers and facilitators to successful implementation. Following this, exploratory trials should be conducted, which ultimately lead to the implementation of a definitive evaluation. Following the six steps of quality intervention development model, this research presents four studies which inform the development and testing of a psychoeducation intervention delivered to Olympic and Paralympic athletes, coaches and athlete support providers prior to their participation in the Rio 2016 Summer Games. There is a gap in the career transition in sport literature pertaining to preventive interventions which this thesis addresses. Additionally, career adaptability skills have yet to be explored in any elite sport context. This thesis also draws the field of implementation science into sport psychology. The first study is a systematic review of the characteristics of the implementation of well-being related interventions in Olympic and Paralympic athletes. The purpose of this study is to review literature which has attempted to enhance the well-being of Olympic and Paralympic athletes and extract data pertaining to the implementation characteristics of the intervention. The findings suggest that to date little consideration has been given to the impact of implementation factors on intervention effectiveness. The second study is a qualitative exploration of the factors Irish Olympic and Paralympic athletes, coaches, and athlete support providers believe affect an athlete`s engagement in a psychoeducation intervention. The key findings suggest for such an intervention to be feasible and acceptable, it should be delivered in group format, at the training location of the athletes, and be packaged as a workshop to assist athletes in adapting to all stages of the Games and should emphasize the benefits to performance. The third study explores the initial efficacy of video as a delivery method for career adaptability psychoeducation with this population. Participants included 168 athletes with a mean age of 26.46 years (N = 116). Additionally, 10 coaches with a mean age of 40.20 years and 47 athlete support providers with a mean age of 39.77 years participated. Informed by entertainment-education theory, a video 155 seconds in length was found to be effective for communicating up to three learning points immediately following viewing. The fourth study explored the transfer of learning from a group-based psychoeducation intervention delivered over the course of a 90-minute workshop. 140 individuals comprised of Olympic and Paralympic athletes, coaches and sport science and medicine support personnel attended the workshop. Of the 140 attendees, ninety-eight attendees consented to participate in the research. Sports represented included Cerebral Palsy football, mixed Paralympic events, hockey, boxing, rugby 7's, athletics, rowing, triathlon, pentathlon, badminton. Overall participants rated the workshops as satisfactory, useful and relevant to their career. Recommendations for the refinement of the intervention and future research were made. A pre-post evaluation of participants` ability to accurately generalize the content of the intervention found significant improvement in thoughts and behaviours following the intervention, with small-large effect sizes calculated. Additionally, less than 20% of all participant`s successfully transferred their learning to the real-world context at two time points following intervention. Overall, participants rated their adaptation to the post-Games career meta-transition positively, and listed skills learned at the workshop as helpful during this adaptation. This thesis contributes to the literature on career adaptability, implementation science, and the practical delivery of career transitions interventions to Olympic and Paralympic populations. Strengths of this thesis lie in the systematic development and testing of a psychoeducation intervention, and in the practical application of career transition theory. Practical recommendations for the development of psychoeducation interventions including both digital video and group format delivery are made.